The Role of the Office of Religious Affairs in Raising Awareness of Converts in Providing Waqf: Case Study in North Morowali Regency (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2022)
This article discusses the role of the Office of Religious Affairs in increasing awareness of converts to giving religious endowment (waqf). In the Islamic tradition, giving waqf is a form of worship oriented toward society’s welfare. However, waqf collection is still constrained by minimal socialization among people who are considered capable. As an institution that has direct contact with the Muslim community, the Office of Religious Affairs has the task of socializing the payment of waqf, including to converts. This research takes a case study in Bahontula Village, North Morowali Regency, where most of the converts in this area come from the upper-middle class. This research is a qualitative study with primary and secondary data collected through observation, interviews, and documentation. The available data were analyzed by data reduction, presentation, and interpretation methods. The results of this study indicate that the local Religious Affairs Office has directly disseminated waqf to converts. Nevertheless, these efforts have not been optimal due to inconsistent allocation of time for the socialization of waqf.